2017
DOI: 10.5296/jsss.v4i2.11386
|View full text |Cite
|
Sign up to set email alerts
|

Female Labor Market Participation and Economic Growth: The Case of Pakistan

Abstract: Female labor force plays a significant role in the economic development of a country. The core objective of this paper is to examine the nexus between female labor force participation rate and Pakistan's economic growth using time series data for the period 1990-2014. The data was extracted from World Development Indicators database. Augmented-Dickey Fuller (ADF) test was applied to examine the data for unit root. The results show that both the variables---female labor force participation rate and economic gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…The ECT is rightly sign and statistically significant at the 1% level which confirms a long-run causality of FLFPR on economic growth. The results are in line with the results of Khaliq et al (2017), Mujahid et al (2013) and Saqib et al (2016), who all saw a long-run causal relationship between FLFPR and economic growth.…”
Section: Hausman Test and Estimate Of Long-run And Short-run Relation...supporting
confidence: 91%
See 1 more Smart Citation
“…The ECT is rightly sign and statistically significant at the 1% level which confirms a long-run causality of FLFPR on economic growth. The results are in line with the results of Khaliq et al (2017), Mujahid et al (2013) and Saqib et al (2016), who all saw a long-run causal relationship between FLFPR and economic growth.…”
Section: Hausman Test and Estimate Of Long-run And Short-run Relation...supporting
confidence: 91%
“…Most empirical studies examined and documented the U-shaped hypotheses by analysing the relationship between FLFPRs and economic development and growth. Khaliq et al (2017) examined the relationship between FLFPR and economic growth in Pakistan using time series data from 1990 to 2014. Using the error correction model (ECM) and Johansen co-integration tests, the results indicated that there exist a long-run and a U-shaped link between economic growth and FLFPR in Pakistan.…”
Section: Empirical Review Of Flfprmentioning
confidence: 99%
“…These results could be attributed to the interplay of preliminary circumstances, economic arrangements, structural transformation, and tenacious gender customs and values in developing economies. Khaliq et al, (2017) observed the node between the female labour force participation and economic growth for Pakistan. The authors employed data for the time span of 1990-2014 and applied the Johensen and ECM methods.…”
Section: Objectives Of the Studymentioning
confidence: 99%
“…Studies of Mincer (1962) and Cain (1966) lead the way to the analysis of the issue in economic literature. Some of those studies' target is to investigate the validity of the U-shaped hypothesis of female labour force function, stating that FLFP decreases over the early stages of industrialization and starts to increase after a threshold level of development is reached (Altuzarra et al, 2019;Gaddis & Klasen, 2014;Goldin, 1995;Khaliq et al, 2017;Kumari, 2018;Luci, 2009;Tam, 2011;Tansel, 2002;Tsani et al, 2013). On the contrary, there are also studies in the literature aiming to investigate the impact of FLFP on per capita GDP or economic growth (Anyanwu et al, 2021;Bloom et al, 2009;Bryant et al, 2004;Gruen & Garbutt, 2003;Verick, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%